Plagiarism: initial research findings in undergraduate students - Kokkinos, Dionysis; Koulouris, Alexandros (Journal of Integrated Information Management, 2019)
Purpose - This paper presents and discusses the main results of a small-scale research concerning students’ and academic staff’s perceptions about plagiarism and its implications. The research was conducted in 2018, at the Department of Archival, Library & Information Studies, University of West Attica, with the use of two separate on-line questionnaires. Design/methodology/approach – The questionnaires, consisted of open and closed-ended questions, were sent respectively to the undergraduate students and to the academic staff of the Department. As a result, 62 questionnaires were completed by the students (~10% of the whole population) and 9 by the academic staff, which was the total number of the faculty members at the time of the study. Findings - The findings demonstrate that the students’ and the academic staff’s comprehension and perception of the term plagiarism, as well as their attitude towards the disciplinary implications, that this phenomenon entails, make it an imperative for academic realm and especially for libraries to deal with it actively and proactively. Originality/value – Useful findings were made regarding the perception and the comprehension of plagiarism phenomenon for undergraduate students.